KONTINUITAS PENGEMBANGAN MISIL BALISTIK IRAN SEBAGAI RESPON TERHADAP DINAMIKA PERSENJATAAN DI KAWASAN TELUK - Fajar Imam Zarkasyi (Dauliyah Journal of Islamic and International Affairs, 2017)
This article focuses on the continuity of Iranian ballistic missile programme afterJCPOA on 2015. The Author argues that the contiunity is related to theconventional arms dynamics which invloved Iran and Gulf Cooperation Council(GCC) countries. By applying action reaction theory, it concludes that themagnitude, timing, and awerness aspects in GCC modernization effort have asignificant impact on Iran decision to continue its ballistic missile programme.By using document analysis as collecting data method, author found many kindof data ilustrating the modernization gap between Iran and GCC and severaldocuments within journal articles and other sources have shown the Iranianthreat perception toward GCC as basis for action reaction model in Iran-GCCrivalry.